Protocol for a multicentre, prospective, open-label, randomised controlled trial to compare PROs and safety outcomes between preoperative and postmastectomy radiotherapy in locally advanced breast cancer patients with immediate reconstruction via a deep inferior epigastric perforator flap (CAPPELLA) in China - Li Zhang; Jiong Wu; Guangyu Liu; Shuang Hao; Jianjing Hou; Changming Zhou; Yifeng Hou; Keda Yu; Zhen Hu; Genhong Di; Zhi Min Shao; Xiaoli Yu (BMJ Open)
Introduction Despite its therapeutic advantages, postmastectomy radiotherapy (PMRT) increases the risk of complications and often leads to poor cosmesis in women undergoing breast reconstruction. Preoperative radiotherapy followed by skin-sparing mastectomy and deep inferior epigastric perforator (DIEP) flap reconstruction is technically feasible, with low rates of surgical complications and good short-term oncological outcomes. Further evaluation in a randomised trial comparing preoperative radiotherapy versus conventional PMRT in breast reconstruction is required to assess both oncological and patient-reported outcomes (PROs).Methods and analysis The CAPPELLA trial is a prospective, multicentre, open-label, randomised controlled trial across nine centres comparing PROs and safety outcomes between preoperative and postoperative radiotherapy in patients with locally advanced breast cancer requiring immediate DIEP flap reconstruction. Female patients aged >18 years with breast cancer who are treated with neoadjuvant systemic treatment, require both mastectomy and radiotherapy and are suitable for DIEP flap reconstruction will be included. Patients will be randomly assigned (1:1) to a preoperative radiotherapy group or a postoperative radiotherapy group. Stratification will be performed by cancer centre at initial diagnosis. The radiation volumes will include the ipsilateral breast/chest wall, supraclavicular lymph nodes, undissected axilla and internal mammary nodes. The dose regimen will be 42.56 Gy in 16 fractions. The primary endpoint will be satisfaction with the breast domain of the BREAST-Q at 2 years postoperatively. The secondary endpoints will include PROs at 3, 12 and 24 months postoperatively in both groups, aesthetic assessment, complication rates, rates of total pathological complete response (tpCR) and tumour safety. All patients will be followed up for 36 months postoperatively. The app software will be used to collect all data prospectively. Data will be analysed using SPSS and Stata software. The target sample size will be 80 participants.Ethics and dissemination This study will be performed according to the Helsinki Declaration. All patients will be asked to provide informed consent before enrolment. Approval for this study was provided by the independent ethics committee and institutional review board of Fudan University Shanghai Cancer Centre. We will present the study results at national and international meetings and publish them in a scientific peer-reviewed journal.Trial registration number NCT05512286.